2019
DOI: 10.1186/s12882-019-1382-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing survival time of hemodialysis patients; time to event analysis using parametric models: a cohort study

Abstract: Background Survival analysis of patients on maintenance hemodialysis (HD) has been the subject of many studies. No study has evaluated the effect of different factors on the survival time of these patients. In this study, by using parametric survival models, we aimed to find the factors affecting survival and discover the effect of them on the survival time. Methods As a retrospective cohort study, we evaluated the data of 1408 HD patients. We considered the data of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 13 publications
3
22
0
3
Order By: Relevance
“…In the analysis of the patient’s blood count, only the leukocyte was an independent prognostic factor for patient survival and its normal to high values (5.81–7.70 and ≥ 7.71) had an HR of, respectively 2.665 (95% CI 1.387–5.119) and 1.435 (95% CI 0.687–2.997). The study by Ebrahimi et al (2019) [ 4 ], confirmed our findings by indicating that as the level of leukocyte count increases, the survival time of patients undergoing HD decreases. A study carried out in Taiwan, showed that the total leukocyte count predicts all causes and cardiovascular mortality in just one year [ 35 ], while in another study carried out in the United States, the reduction in the lymphocyte count are risk factors for mortality [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the analysis of the patient’s blood count, only the leukocyte was an independent prognostic factor for patient survival and its normal to high values (5.81–7.70 and ≥ 7.71) had an HR of, respectively 2.665 (95% CI 1.387–5.119) and 1.435 (95% CI 0.687–2.997). The study by Ebrahimi et al (2019) [ 4 ], confirmed our findings by indicating that as the level of leukocyte count increases, the survival time of patients undergoing HD decreases. A study carried out in Taiwan, showed that the total leukocyte count predicts all causes and cardiovascular mortality in just one year [ 35 ], while in another study carried out in the United States, the reduction in the lymphocyte count are risk factors for mortality [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…The median survival time was 6.79 ± 0.37 years (mean ± standard deviation), and 254 (60.2%) patients died. In the study by Nyuyen et al (2017) [ 23 ] the survival time was 5.27 ± 0.31 years (mean ± standard deviation), in the study by Browne et al (2014) [ 1 ] the death rate was 60%, in the study by Ebhahimi et al (2019) [ 4 ] of 52% and in the study by Chandrashekar et al (2014) [ 24 ] 19.8% over 2 years. These periods are relatively short when compared to US rapporteurs [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations